The evaluation of problem-solving oriented e-module in learning computer-based subject - Noor Hidayah Che Lah; Mashitoh Hashim; Jamalludin Harun; Yusri Abdullah (Institute of Advanced Engineering and Science, 2024)
It is tough and challenging to learn several computer-based subjects via an online learning setting during COVID-19 for students from the education field. It required a lot of skills, techniques, understanding among students, and the ability to think critically to solve problems. To date, a lack of studies provides digital content as learning approaches to computer-based subject students for their learning via online learning. Thus, the problem-solving oriented e-module in learning computer-based subject via Facebook for Higher Education was proposed. An exploratory sequential research design (qualitative and then quantitative approach) has been used in this study. Research samples were selected based on purposive sampling (10 students) to find out what they needed from the e-module. Then, the module was developed based on ADDIE Model and problem-solving learning strategy. There were nine experts validated the e-module in terms of the ADDIE model approach, problem-solving approach, and content. This module was tested on 34 undergraduate students towards students’ performance and social presence for quantitative part. The t-test showed that the e-module significantly improved student performance (p 0.00; t=5.52) with Cohen’s d=0.944. Interestingly, the results from the content analysis show that this module fosters social presence via Facebook learning groups such as interactive, affective, and cohesive.